2013
DOI: 10.1002/adfm.201303138
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous NiCo2O4 Nanowire Arrays Grown on Carbon Textiles as Binder‐Free Flexible Electrodes for Energy Storage

Abstract: Binary metal oxides has been regarded as a promising class of electrode materials for high‐performance energy storage devices since it offers higher electrochemical activity and higher capacity than mono‐metal oxide. Besides, rational design of electrode architectures is an effective solution to further enhance electrochemical performance of energy storage devices. Here, the advanced electrode architectures consisting of carbon textiles uniformally covered by mesoporous NiCo2O4 nanowire arrays (NWAs) are succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
417
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 735 publications
(432 citation statements)
references
References 51 publications
13
417
2
Order By: Relevance
“…45,46,56 In addition, although good cycling performance has been achieved for NiCo 2 O 4 , it suffers from low capacitance, especially the high-rate capacitance. 14,54,57 In this work, the supercapacitor performances of NiCo 2 O 4 NS/3DGN, especially the rate capability and long-term cycling stability, are much better than those of many other pseudocapacitor electrode materials (Table S1 in ESI †). The excellent electrochemical performances of NiCo 2 O 4 NS/3DGN could be ascribed to the following factors.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…45,46,56 In addition, although good cycling performance has been achieved for NiCo 2 O 4 , it suffers from low capacitance, especially the high-rate capacitance. 14,54,57 In this work, the supercapacitor performances of NiCo 2 O 4 NS/3DGN, especially the rate capability and long-term cycling stability, are much better than those of many other pseudocapacitor electrode materials (Table S1 in ESI †). The excellent electrochemical performances of NiCo 2 O 4 NS/3DGN could be ascribed to the following factors.…”
mentioning
confidence: 82%
“…The pseudocapacitor undergoes reversible redox reaction that occurs in the electrode materials, such as metal oxides (RuO 2 , MnO 2 , Co 3 O 4 , NiCo 2 O 4 , CoMoO 4 , etc.) [7][8][9][10][11][12][13][14][15][16] and metal hydroxides (Co(OH) 2 , Ni(OH) 2 , etc. ); [17][18][19] it stores more charges and provides higher specific capacitance than does the EDLC.…”
mentioning
confidence: 99%
“…The irreversible capacity loss for the first cycle can be attributed to the formation of an SEI layer and possible incomplete restoration of metallic Ni and Co into the original sulfide, an effect that has been commonly observed in NiCo 2 O 4 electrode materials. 22,35 In the second and third cycles, the discharge capacities of the electrode decreased to 1912 mAh g − 1 and 1891 mAh g − 1 , respectively, and the corresponding Coulombic efficiency increased to 98.1% and 98.8%, respectively. The sharp increase in Coulombic efficiency indicates that a stable SEI layer had already formed during the initial cycles.…”
Section: D-networked Nico 2 S 4 Nsas As Anodes In Libsmentioning
confidence: 99%
“…16,17 Recently, direct growth of self-supported NiCo 2 O 4 nanowires and ZnCo 2 O 4 nanowire arrays on current-collecting substrates has been shown to overcome the drawbacks of mixing active electrode materials with conductive additives and binders and to increase endurance of fast charge and discharge processes. 22,23 Furthermore, it has been reported that 3D network structures (for example, graphene networks, 7 MO/3D graphene network composites 24 and diamond/ carbon nanotubes 25 ) can provide open channels for efficient electron/ ion transport and large surface area for reactions, both of which are favorable properties for materials and devices used in electrochemical applications. In this work, we report the synthesis of 3D-networked NiCo 2 S 4 nanosheet arrays (NSAs) directly on carbon cloth and their application as an anode material in LIBs; to our knowledge, this is the first such demonstration.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, large specific surface area will provide more electroactive sites for the Faradaic reactions, and load more doublelayer charges. Along such idea, many kinds of nanomaterials, [9][10][11] especially hollow spheres, 12 have been developed to improve pseudocapacitors, but the increased contact resistance often emerges in these porous materials. On the other hand, increasing conductivity will greatly favor the Faradaic reactions, which has been demonstrated typically in the integration of oxides with metal foam, 13 carbon cloth, 9 graphene and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%